The Explanation of Nature of Religion in the Works of First Marxist Atheists in Lithuania - Mikuckas, Petras (Problemos, 1984)
In the article an analysis of general theoretic conception of religion and an explanation of its nature in the works• of first Marxist atheists in Lithuania is presented. A pattern of structural conception of this complex social phenomenon is reconstructed. Another task set by the author is to show how much the proletarian atheists were able, from the materialistic standpoint, to expose the scientific groundlessness of both objective-idealistic (theological) and subjective-idealistic conceptions on the essence of religion.